The Decline of the Virginia (and American) Death Penalty - Heedman, Hanna (2014)
The American death penalty is disappearing. Death sentences and executions have reached the lowest levels seen in three decades. Even the states formerly most aggressive in pursuit of death sentences have seen death sentences steadily decline. Take Virginia, which has the highest rate of executions of any death penalty state, and which has executed the third highest number of prisoners since the 1970s. How times have changed. There has not been a new death sentence in Virginia since 2011. Only seven counties have imposed death sentences in the past decade in Virginia. There are now two or fewer trials a year at which a judge or jury considers imposing the death penalty. Still more surprising, at over one half of those trials the judge or jury chooses a sentence of life without parole (eleven of twenty-one cases from 2005 to 2015 at which there was a capital sentencing hearing resulted in a life sentence). Why is this happening-and in Virginia of all places? In this study, I examine every capital trial from 2005 to 2015-twenty-one trials-and I compare a group of twenty capital trials from 1996 to 2004. The law on the books has not meaningfully changed. However in 2004, the legislature created regional defense resource centers to handle capital cases. From 1996 to 2004, the crucial sentencing phase, at which the judge or jury decided whether to impose the death penalty, was typically cursory, averaging less than two days long. In the more recent trials, the average was twice that-four days-and still more striking was the increase in the numbers of defense witnesses called, the greater use of expert witnesses, and the added complexity of sentencing proceedings. Improved capital defense resources may explain this sharp and sudden decline in death sentences. North Carolina, which created a similar state capital defense resource office, experienced a decline that tracks Virginia's, and yet in states like Florida, lacking statewide defense resources, the rate with which death sentences are imposed has remained fairly stable. This evidence: (1) raises heightened Eighth Amendment arbitrariness concerns with the scattered state of the American death penalty, including that death sentences may result from local failures to provide adequate defense resources; (2) demonstrates that those same failures implicate Sixth Amendment ineffective assistance of counsel claims in individual cases and in systematic challenges in states that fail to provide adequate resources; and (3) strongly supports the establishment of statewide capital-and non-capital-public defender offices